Blue Light-Reducible Cytochromes in Membrane Fractions from Neurospora crassa - Borgeson, Charlotte E. (1985)
We have assayed absorbance changes generated by blue light in plasma membranes, endoplasmic reticulum, and mitochondrial membranes from Neurospora crassa. Light minus dark difference spectra, obtained anaerobically in the presence of ethylenediaminetetraacetate, indicated that b-type cytochromes could be photoreduced in all three membranes. In plasma membranes, a b-type cytochrome with a distinct difference spectrum was photoreducible without addition of exogenous flavin. Addition of riboflavin greatly stimulated the photoreduction of cytochromes in endoplasmic reticulum and mitochondrial membranes. In its spectral characteristics the cytochrome on the endoplasmic reticulum resembled cytochrome b(5) or nitrate reductase, while the cytochrome in mitochondrial membranes had the same spectrum as cytochrome b of the mitochondrial respiratory chain. Cytochromes in the three membrane fractions reacted differently to blue light in the presence of various inhibitors. Potassium azide inhibited reduction of plasma membrane cytochrome b, with 50% inhibition at 1.0 millimolar. The same concentration of azide stimulated photoreduction of cytochromes in both endoplasmic reticulum and mitochondria. Although photoreduction of cytochromes in all three membranes was inhibited by salicylhydroxamic acid, cytochromes in plasma membranes were more sensitive to this inhibitor than those in endoplasmic reticulum and mitochondria. Cells grown to induce nitrate reductase activity showed an elevated amount of blue light-reducible cytochrome b in the endoplasmic reticulum.